2009
DOI: 10.1016/j.wasman.2008.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of behavior of endocrine-disrupting chemicals in leachate treatment process and evaluation of removal efficiency

Abstract: An experimental study of the behavior of endocrine-disrupting chemicals (EDCs) in leachate treatment processes (aeration, coagulation and sedimentation, activated carbon adsorption, and advanced oxidation) was conducted and removal efficiencies were evaluated. Among target EDCs, concentrations of BPA (1800 times), DBP (10 times), BBP (40 times), and DEHP (30 times) in leachate are more than ten times higher than those in surface water. BPA, DBP, and BBP can be treated by aeration and DEHP, by advanced oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Several studies (Asakura and Matsuto, 2009;Foo et al, 2013a;Papastavrou et al, 2009) use batch adsorption to evaluate the performance of activated carbon. Though batch adsorption studies provide vital equilibrium data on removal of pollutants from landfill leachate, column adsorption studies provide a more realistic representation of the use of carbon adsorption in real practice.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Asakura and Matsuto, 2009;Foo et al, 2013a;Papastavrou et al, 2009) use batch adsorption to evaluate the performance of activated carbon. Though batch adsorption studies provide vital equilibrium data on removal of pollutants from landfill leachate, column adsorption studies provide a more realistic representation of the use of carbon adsorption in real practice.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical analysis can serve as a useful tool to identify a group of EEs in leachate, by which the possible source of these compounds can be investigated. In this study, 5 identified EEs (4- t -OP, BPA, D n BP, DEP, and DEHP) were detected in leachate samples collected from selected landfill sites, and high detection rates have been frequently reported for them in previous studies [11], [12], [17]. 4- t -OP is the most representative final breakdown product of alkylphenol polyethoxylates (APEOs), which are widely used as wetting and emulsion agents in industrial and household applications [33].…”
Section: Discussionmentioning
confidence: 93%
“…Chemical analysis is a rapid and sensitive screen to measure a large number of compounds. A variety of chemical analysis methods, such as gas chromatography-mass spectrometry (GC-MS) [11], [12], gas chromatography-flame ionization detector (GC-FID) [13], and high performance liquid chromatography (HPLC) [14], have been developed to identify estrogenic substances that potentially interfere with the reproductive system. Based on several combinations of instruments and detectors, the analytical results could provide excellent quantitative information of target compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment technologies for these EDCs in high-moisture sludge have limitations, hence needing more efforts on tackling complex wastewater treatment (Asakura and Matsuto, 2009). One of the promising technologies is the use of advanced oxidation processes (AOPs).…”
Section: Introductionmentioning
confidence: 99%